Ten-Year Results of Inguinal Hernia Open Mesh Repair - Ceith Nikkolo; Ceith Nikkolo; Toomas Lillsaar; Tiit Vaasna; Tiit Vaasna; Ülle Kirsimägi; Ülle Kirsimägi; Urmas Lepner; Urmas Lepner (Journal of Abdominal Wall Surgery)
IntroductionThe primary aim of the present prospective study was to determine the clinical recurrence rate of inguinal hernia at a 10-year follow-up. Other aims included evaluating the recurrence rate based on ultrasound (US) examination and assessing chronic pain and foreign body feeling following open inguinal hernia repair.MethodsA pain questionnaire was completed 10 years after surgery. At the follow-up visit, the patients were examined for a recurrent hernia. For patients who completed a 10-year follow-up and did not have clinical hernia recurrence, an ultrasound of the inguinal canal was performed in addition to a clinical examination.ResultsThe data of 242 patients were analyzed at 10-year follow-up. At the 3-year follow-up, three clinical recurrences were diagnosed. Additionally, two recurrences were diagnosed between the 6-month and 3-year follow-up visits, and three were diagnosed between the 3-year and 10-year follow-up visits. At the 10-year follow-up visit, seven recurrences were clinically diagnosed, and in twenty-three cases, ultrasound detected recurrent inguinal hernias that were not clinically detectable. Of the patients, 94.5% (95% CI 91.8%–97.2%) are recurrence-free at the 10th postoperative year. Of the patients, 18.6% (95% CI, 14.0–24.2) experienced pain in the inguinal area during various activities, including at rest, upon coughing, when rising from a lying to a sitting position, and during physical activities. The mean VAS score was 37.6 (SD 21.5), based on the highest VAS score during different activities. Of the fifteen patients with clinically recurrent hernias, 66.7% reported pain during various activities. In contrast, the rate of chronic pain among patients without clinical hernia recurrence was significantly lower at 15.4% (p < 0.001). Of the twenty-three patients with US recurrence, 17.4% experienced pain in the inguinal area. The respective result among patients without US and clinical recurrence was 15.2% (p = 0.763). Foreign body feeling was reported by 26 patients (12.8%) without hernia recurrence, by three patients (20%) with clinical recurrence, and by two patients (8.7%) with ultrasound recurrence (p = 0.560).ConclusionConsidering the high rate of late recurrences, a follow-up of at least 10 years is necessary to determine the accurate recurrence rate after open inguinal hernia mesh repair. Further studies are needed to clarify the significance of US recurrences.Clinical Trial Registrationclinicaltrials.gov, identifier NCT06008535.